Psychoanalytic and Crime: Is Freud's Theory Still Applicable in Criminological Research? - Zul Khaidir Kadir (Media Keadilan: Jurnal Ilmu Hukum, 2024)
Freud's psychoanalysis emphasizes that human behavior, including criminal behavior, is driven by unconscious conflicts that arise from the dynamics between the three main components of personality, namely the id, ego, and superego. Since its introduction in the early 20th century, the relevance of this theory has begun to be questioned along with the development of modern criminology. One of the main reasons why Freud's psychoanalytic theory began to face challenges is because of the increasingly clear gap between the individualistic approach faced with the need to explain more complex crime phenomena in the modern era. This study uses a data collection method collected using library research, then analyzed using qualitative methods and presented descriptively. The results of the study indicate that Freud's psychoanalytic theory still has relevance in criminology, especially in understanding the deep psychological motivations behind certain criminal behavior. However, to understand the criminal phenomenon as a whole, integration between psychoanalysis and contemporary criminological theories is needed. This approach would make it possible to combine the understanding of individual psychological motivations offered by psychoanalysis with external factors such as social and economic pressures explained by other theories.